Implementing e-commerce strategies : a guide to corporate success after the Dot.com bust - Epstein, Marc J. (Westport, Connecticut ( London) : Praeger, 2004)
"In Implementing E-Commerce Strategies, Marc Epstein goes beyond the hype to focus on the practical angles of designing, executing, and successfully managing an e-commerce strategy that works for your company. While many books have addressed the "what" and "why" of e-commerce, Epstein zeroes in on the elusive "how.""--BOOK JACKET.
I: Increasing the return on E-commerce investments -- Characteristics of E-commerce success -- Corporate and functional E-commerce leadership -- Formulating an E-commerce strategy -- Organizational structure and design for E-commerce -- Management systems for E-commerce success -- Measuring the payoffs of E-commerce investments -- II: Company cases -- Company cases: B2C--retail -- Company cases: B2C--services -- Company cases: B2B -- Achieving success in E-commerce.
Includes bibliographical references (p. [189]-203) and index.
Management
Keywords: Electronic commerce; Strategic planning; Business enterprises -- Computer networks -- Planning; Electronic commerce -- Case studies; Guide (Descripteur de forme)